Usia menarche sebagai faktor risiko terhadap kejadian preeklamsia dan eklamsia - Astrid Kizy Primadani; Elisabeth S Herini; Djaswadi Dasuki (Berita Kedokteran Masyarakat (BKM), 2018)
Age of menarche as a risk factor for preeclampsia and eclampsiaPurposeThe purpose of this study is to determine the effect of menarche age on the incidence of preeclampsia and eclampsia.MethodThe observational study with the case-control design was conducted involving 90 pregnant and postpartum women. The bivariable analysis used T-test and McNemar test, while multivariable analysis using conditional logistic regression. Results The average age of menarche in the preeclampsia group was one year younger than the non-preeclampsia group. Any increase in one year of age of menarche lowers the risk of preeclampsia and eclampsia by 78%. Risk factors for preeclampsia are increased in pregnant women at age> 35 years and have body mass index before pregnancy> 25 kg/m2.ConclusionThere is a significant relationship between age of menarche and the incidence of preeclampsia and eclampsia. Body mass index before pregnancy is a confounding factor of the association between age of menarche and the incidence of preeclampsia and eclampsia.